Complete in vitro Dissolution of Valbenazine as Either Whole Capsules or Crushed Capsule Contents. (April 2023) - Hebert, Mello; Moore, Richard; Jen, Eric; Siegert, Scott
Abstract: Introduction: Tardive dyskinesia (TD) is a persistent and potentially disabling movement disorder associated with exposure to antipsychotics and other dopamine receptor blocking agents. Three valbenazine capsule strengths (40 mg, 60 mg, 80 mg) are approved for the once-daily treatment of TD. However, some patients with TD, especially in elderly populations, have trouble swallowing due to orolingual movements. This study was conducted to evaluate two different dissolution methods for valbenazine: whole intact capsules versus crushed capsule contents. Methods: Samples were prepared using two commercial lots (Lot-A, Lot-B) for two doses (40 mg, 80 mg), with six replicate samples per lot and dose. The whole capsules were weighed, put into a sinker, and added to a dissolution bath containing 900 mL of 0.1N HCl at 37±0.5° Celsius. Testing on the crushed capsule contents commenced after opening the capsules, weighing and crushing the contents, and transferring the contents to the dissolution bath. Samples were collected (at 10, 15, 20, 30, 45, and 60 min) with a paddle speed of 50 rpm and analyzed using high performance liquid chromatography. Standards were prepared at nominal concentrations of 0.044 mg/mL (for 40 mg) and 0.089 mg/mL (for 80 mg). Results: Capsules were opened easily by manual manipulation, and contents were crushed easily between spoons. Very rapid (>85% in 15 min) and complete drug release was observed in all samples, independent of capsule strength (40 mg, 80 mg) or preparation (whole intact capsule or crushed capsule contents). For 40-mg capsules, average percent release at first and last collection timepoints were as follows (whole vs crushed): 10 min (98.4% vs 98.6% [A], 93.7% vs 97.6% [B]); 60 min (102.3% vs 100.5% [A], 100.9% vs 100.6% [B]). Results for 80-mg capsules were as follows: 10 min (98.2% vs 99.6% [A], 99.4% vs 97.9% [B]); 60 min (102.0% vs 101.6% [A], 103.2% vs 100.9% [B]). Conclusions: Crushing the capsule contents did not impact the in vitro dissolution performance of valbenazine. Many patients with TD, particularly elderly patients, have difficulty swallowing and may benefit from alternative delivery methods for valbenazine, especially if other TD medications cannot be crushed. More research is needed to better understand if and how crushing the capsule contents of valbenazine affects their stability when mixed with food or delivered through a feeding tube. Funding: Neurocrine Biosciences, Inc.